Ozone-Free Synthesis of Ozonides: Assembling Bicyclic Structures from 1,5-Diketones and Hydrogen Peroxide - Yaremenko, Ivan A; Gomes, Gabriel dos Passos; Radulov, Peter S; Belyakova, Yulia Yu; Vilikotskiy, Anatoliy E; Vil’, Vera A; Korlyukov, Alexander A; Nikishin, Gennady I; Alabugin, Igor V; Terent’ev, Alexander O (Journal of organic chemistry, 2018)
Reactions of 1,5-diketones with H2O2 open an ozone-free approach to ozonides. Bridged ozonides are formed readily at room temperature in the presence of strong Brønsted or Lewis acids such as H2SO4, p-TsOH, HBF4, or BF3·Et2O. The expected bridged tetraoxanes, the products of double H2O2 addition, were not detected. This procedure is readily scalable to produce gram quantities of the ozonides. Bridged ozonides are stable and can be useful as building blocks for bioconjugation and further synthetic transformations. Although less stabilized by anomeric interactions than bis-peroxides, ozonides have an intrinsic advantage of having only one weak O–O bond. The role of the synergetic framework of anomeric effects in bis-peroxides is to overcome this intrinsic disadvantage. As the computational data have shown, this is only possible when all anomeric effects in bis-peroxides are activated to their fullest degree. Consequently, the cyclization selectivity is determined by the length of the bridge between the two carbonyl groups of the diketone. The generally large thermodynamic preference for the formation of cyclic bis-peroxides disappears when 1,5-diketones are used as the bis-cyclization precursors. Stereoelectronic analysis suggests that the reason for the bis-peroxide absence is the selective deactivation of anomeric effects in a [3.2.2]tetraoxanonane skeleton by a structural distortion imposed on the tetraoxacyclohexane subunit by the three-carbon bridge.